Financial Support Between Spouses: An Analytical Study of the Principles of Kind Treatment and Rights and Duties - Mohammed Hasan, Baidar Mohammed; Wan Ismail, Wan Abdul Fattah; Abdul Rab, Muneer Ali; Hashim, Hasnizam (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2025)
This study explores the concept of